HOUSE ENVIRONMENTS AS RISK FACTORS OF TUBERCULOSIS IN CILACAP DISTRICT - Imam Agus Faizal; Ira Pangesti; Denih Agus Setia P (Jurnal Riset Kesehatan, 2021)
Tuberculosis (TB) is a disease caused by the bacterium Mycobacterium tuberculosis which is still a major global health problem in the world and causes morbidity rates in millions of people each year. new cases of positive BTA in Central Java in 2017 amounted to 60.91 per 100,000 population. Meanwhile, based on the profile of the Cilacap District Health Office in 2018, the number of TB sufferers reached 5271 cases, around 1089 TB cases that have not been found and reported, while 34 of them died. The purpose of this study was to analyze the risk factors for tuberculosis incidence in Cilacap Regency. The purpose of this study was to analyze House Environments As Risk Factors Of Tuberculosis In Cilacap District. This type of research is an observational analytic quantitative approach with a research design that is using case control and cross-sectional which was conducted from May 2020 to June 2020 in the work area of the RSUD Cilacap Paru Center. The Respondents this research is the person who lived in the work area of the public health center using total sampling technique so that it is obtained 30 respondents. This study concludes significant effect on floor types, natural ventilation and housing density. Meanwhile, the respondent's characteristic factors such as smoking habit, phlegm discharge habit and coughing and sneezing influenced the incidence of tuberculosis.